Določitev območij poselitve v Sloveniji po vodnogospodarskih vidikih - Gosar, Leon (Urbani izziv, 2004)
Enforcement of the European Union's legal order is bringing substantial expertinvolvement even in water management. The main act, the Water Framework Directive (WFD), is followed by numerous others. Substantial investments will be demanded even in Slovenia to comply with the Uniform Waste Water Treatment Directive (UWWTD) and Integrated Pollution Prevention and Control Directive (IPPCD). On the operative utilities are dealt with by municipalities, while states have to fulfil national responsibilities to the EU. Timely achievement of goals demands coordinated activities based on expert guidelines. One of UWWTD's basic parameters is the agglomeration, which is a uniform area of suchcompact settlement, to which special stipulations and dynamics from the directive can be applied. The criteria for compactness is population density per hectare. A suitable grid of square one-hectare cells was devised for Slovenia, with three types of settlement cells. Areas of particular agglomerations are formed by two adjoining cells whose population is most dense. The area of agglomerations is much smaller than settlement area in the register of territorial units, thus Slovene summary obligations from the directive are much smaller, as was shown in the expert guidelines for the National programme for collecting and treating waste communal and atmospheric water. These agglomerations are the basic element for planning and intervention even in other water resource planning (flood prevention measures etc.) and could also be used for programmes of provision of utilities, as wellas other physical development plans.
Keywords: komunalna infrastruktura; naselja; odpadne vode; oskrba z vodo; poselitev; vodno gospodarstvo